2018
DOI: 10.1371/journal.pone.0202053
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up between 6 and 24 months after discharge from treatment for severe acute malnutrition in children aged 6-59 months: A systematic review

Abstract: BackgroundSevere acute malnutrition (SAM) is a major global health problem affecting some 16.9 million children under five. Little is known about what happens to children 6–24 months post-discharge as this window often falls through the gap between studies on SFPs and those focusing on longer-term effects.MethodsA protocol was registered on PROSPERO (PROSPERO 2017:CRD42017065650). Embase, Global Health and MEDLINE In-Process and Non-Indexed Citations were systematically searched with terms related to SAM, nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Treatment guidelines have also changed since 1987, which means that the results of their study may need to be re‐evaluated. Although data on the mortality and relapse to SAM of children managed in Community‐Based Management of Acute Malnutrition programmes (uncomplicated SAM) have been reported (O'Sullivan, Lelijveld, Rutishauser‐Perera, Kerac, & James, ; Stobaugh et al, ), only a few papers reported nutritional outcomes of children after treatment from cSAM (Fergusson et al, ; Kerac et al, ; Kerac et al, ; Lelijveld et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment guidelines have also changed since 1987, which means that the results of their study may need to be re‐evaluated. Although data on the mortality and relapse to SAM of children managed in Community‐Based Management of Acute Malnutrition programmes (uncomplicated SAM) have been reported (O'Sullivan, Lelijveld, Rutishauser‐Perera, Kerac, & James, ; Stobaugh et al, ), only a few papers reported nutritional outcomes of children after treatment from cSAM (Fergusson et al, ; Kerac et al, ; Kerac et al, ; Lelijveld et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies explicitly noted that children that relapsed to SAM were readmitted to the hospital although any clinical comorbidities were not specified (Khanum et al, 1998;van Roosmalen-Wiebenga et al, 1987). In the study of Khanum et al (1998) Kerac, & James, 2018;Stobaugh et al, 2018), only a few papers reported nutritional outcomes of children after treatment from cSAM (Fergusson et al, 2009;Kerac et al, 2009;Kerac et al, 2014;Lelijveld et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up can potentially help individuals avoid developing SAM, while a more individualized approach to the treatment of both forms of malnutrition can improve recovery outcomes and reduce relapses. O’Sullivan et al’s (2018) systemic review of the literature on post-treatment reveals that more studies are needed that chronicle post-treatment recovery. They raise the concern over RUTF treatment schedules, which they argue may need to be more flexible depending on the individual circumstances.…”
Section: Resultsmentioning
confidence: 99%
“…Lenter (2013) focuses on how effective the WHO protocol has been in treating SAM with RUTFs compared to standard care, setting a benchmark for future studies. More recently, contributions to the field include the state of RUTFs and Ready to Use Supplementary Foods (RUSFs) 2 used specifically in Ethiopia (Ersino et al, 2018), O’Sullivan et al’s (2018) review of literature published on recovery rates post-discharge of SAM treatment, and a systemic review of the effectiveness of using RUTF interventions during the rehabilitation phase of SAM by NGO Campbell Collaboration (Schoonees et al, 2019). These reviews highlight not only the successes of RUTFs in treating SAM in children living in low and medium income countries, but also acknowledge that improvements can be made to RUTF formulations as well as how and when they are administered.…”
Section: Introductionmentioning
confidence: 99%
“…Following discharge from inpatient treatment at NRUs, children with SAM have a high risk of mortality, poor nutritional outcomes including stunting and recurrence of malnutrition, and inhibited development which is longlasting 22,24,[34][35][36][37] . Based on the results of this survey, NRUs in Malawi require additional investment in comprehensive interventions to improve outcomes in these most vulnerable children.…”
Section: Future Directionsmentioning
confidence: 99%